2013
DOI: 10.1017/s0376892913000520
|View full text |Cite
|
Sign up to set email alerts
|

Large scale spatio-temporal patterns of road development in the Amazon rainforest

Abstract: SUMMARYThere is burgeoning interest in predicting road development because of the wide ranging important socioeconomic and environmental issues that roads present, including the close links between road development, deforestation and biodiversity loss. This is especially the case in developing nations, which are high in natural resources, where road development is rapid and often not centrally managed. Characterization of large scale spatio-temporal patterns in road network development has been greatly overloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
0
12
0
4
Order By: Relevance
“…Furthermore, the recent return to increasing deforestation rates seems likely to continue as a newly appointed administration led by President Jair Bolsonaro (inaugurated 1 January 2019) threatens to expand mining, pasture, and agricultural activities in the Amazon (Artaxo, 2019;Escobar, 2018). Amazon road networks are also anticipated to continue expanding (Ahmed, Ewers, & Smith, 2013;Ahmed et al, 2014;Ahmed, Souza, Riberio, & Ewers, 2013;Laurance et al, 2014). A recent analysis across the entire Brazilian Amazon found that, on average, nearly 17,000 km of roads were added every year between 2004 and 2007 (Ahmed, Souza, et al, 2013).…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…Furthermore, the recent return to increasing deforestation rates seems likely to continue as a newly appointed administration led by President Jair Bolsonaro (inaugurated 1 January 2019) threatens to expand mining, pasture, and agricultural activities in the Amazon (Artaxo, 2019;Escobar, 2018). Amazon road networks are also anticipated to continue expanding (Ahmed, Ewers, & Smith, 2013;Ahmed et al, 2014;Ahmed, Souza, Riberio, & Ewers, 2013;Laurance et al, 2014). A recent analysis across the entire Brazilian Amazon found that, on average, nearly 17,000 km of roads were added every year between 2004 and 2007 (Ahmed, Souza, et al, 2013).…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…Served by new roads, infrastructure and mining projects in Brazil have shaved 4.41 million hectares from protected areas in the lowland Amazon since 2008 [7]. In western Amazonia, a central-government decision to drill for oil in Ecuador's biodiversity rich Yasuni National Park has generated heated controversy [8], paving the way to a growing road network in that region [9]. Even a cursory glance across 58 tropical and subtropical nations shows over a fifth of 373 national parks (the reserve category with one of IUCN's highest forms of protection) are traversed by one or more main roads, and one in twelve by highways, with Asian protected areas suffering disproportionately (Table 1).…”
Section: Where Do You Feel the Most Relaxed?mentioning
confidence: 99%
“…While it is clearly desirable to have a dynamic road model integrated with deforestation models, it is not so clear that an untested road model represents an improvement over the use of static road networks alone. There are road modelling approaches that have been validated (Arima et al ., , ; Ahmed et al ., ; Walker et al ., ), and we expect that the future of tropical LULC change modelling will begin to incorporate such advances.…”
Section: Discussionmentioning
confidence: 99%